Differences in global, regional, and national time trends in disability-adjusted life years for atrial fibrillation and flutter, 1990–2019: an age-period-cohort analysis from the 2019 global burden of disease study - Tang, Juan; Zhang, Qingwei; Peng, Shengxian; Li, Huan; Hu, Weike; Hao, Min; Liu, Yue; Sun, Mengyan; Cao, Wenzhai; Yin, Niying; Liu, Xiaozhu; Xu, Te (Frontiers in Cardiovascular Medicine, 2024)
Background Atrial fibrillation and flutter, collectively referred to as AF/AFL, pose substantial public health challenges across nations of different economic statuses. Abjective This research is intended to assess the discrepancies in global, regional, and national trends in DALYs for atrial fibrillation and flutter throughout 1990 and 2019. Methods The GBD 2019 report included statistics on AF/AFL. An age-period-cohort (APC) model was used to calculate the changes in DALYs from ages 30 to 34 years up to 95 + years. The model calculated both net drifts and local drifts in DALYs. In addition, we analysed the relative risks for certain time periods and birth cohorts from 1990 to 2019 in order to assess their impact. In order to measure the changes over time in the age-standardized rate (ASR) of DALYs caused by AF/AFL, we calculated the average annual percentage changes (AAPCs) based on age, gender, socio-demographic index (SDI), and location. This approach enables us to analyse the impact of age, period, and cohort on trends in DALYs, which may uncover disparities in the management of AF/AFL. Results The global number of DALYs cases was 8,393,635 [95% uncertainty interval (UI): 6,693,987 to 10,541,461], indicating a 121.6% rise (95% UI: 111.5 to 132.0) compared to 1990. From 1990 to 2019, the worldwide ASR of DALYs decreased by 2.61% (95% UI −6.9 to 1.3). However, the other SDI quintiles, except for high SDI and high-middle SDI, had an increase. During the last three decades, high-income nations in the Asia Pacific region had the most significant reduction in ASR of DALYs, whereas Central Asia experienced the highest rise (with a net drift of −0.9% [95% Confidence Interval (CI): −1.0 to −0.9] and 0.6% [95% CI: 0.5 to 0.7], respectively). Approximately 50% of the burden of AF/AFL has been transferred from areas with high and high-middle SDI to those with lower SDI. There was an inverse relationship between the AAPC and the SDI. In addition, men and older individuals were shown to have a greater burden of AF/AFL DALYs. Conclusion The findings of this research demonstrate that the worldwide impact of AF/AFL remains significant and increasing, with the burden differing depending on SDI. The exhaustive and comparable estimates provided by these results may contribute to international efforts to attain equitable AF/AFL control.